Honen's Senchakushu: Passages on the Selection of the Nembutsu in the Original Vow (Senchaku hongon nembutsu shu). - Dankert, Michael J. (Buddhist Studies Review, 2003)
Honen's Senchakushu: Passages on the Selection of the Nembutsu in the Original Vow (Senchaku hongon nembutsu shu). University of Hawai'i Press, Honolulu 1998, xiii, 280 pp. Hb $55.00, ISBN 0-8248-2025-8; pb $29.95, ISBN 0-8248-2110-6.